(3GdeUWdM GdGLJeGYj hGdHQfGeL Gdbhj aj VhA GdeQMdI GdMVGQjI (B:s (3OGQSI JWHjbjI ddhGbY GdGLJeGYj GdYQGbj (B/s - (3GdLHhQj, Tajb EHQGgjes ((3YeGf, GdCQOf (B:s (3OGQ ZjOGA ddfTQ hGdJhRjY (B:s (3OGQ GdeYQaI ;s, 2020)
(3jMJhj cJGH GdeUWdM GdGLJeGYj hGdHQfGeL Gdbhj aj VhA GdeQMdI GdMVGQjI OGQSI JWHjbjI ddOcJhQ Tajb EHQGgje UGdM GdLHhQj Ydi SHYI CbSGe hge HGdJQJjH Gdeaghe hGdHfGA ddeQMdI GdMVGQjI, GdeQMdI GdMVGQjI GdYGdejI hGdYQGbjI, LOd GdeQMdI GdMVGQjI hGdeUWdM GdYdej GdGLJeGYj, GdHQfGeL Gdbhj aj Yde GdGMJeGY, GdHQfGeL Gdbhj aj GdeLJeY GdYQGbj, GdHQfGeL Gdbhj hGdhGbY GdGLJeGYj GdYQGbj HYO GdEMJdGd GdCeQjcj, Gdhge GdGLJeGYj hGdeQMdI GdMVGQjI hGdHQfGeL Gdbhj aj OQGSI GdhGbY GdGLJeGYj GdYQGbj(B.s
(3HHdjhLQGajI (B: (3UaMI (B129-130.s
Keywords: (3GdYQGbs -- (3CMhGd GLJeGYjIs; (3GdYQGbs -- (3JGQjNs